2021
DOI: 10.3390/nu13041058
|View full text |Cite
|
Sign up to set email alerts
|

i-Rebound after Stroke-Eat for Health: Mediterranean Dietary Intervention Co-Design Using an Integrated Knowledge Translation Approach and the TIDieR Checklist

Abstract: Lifestyle interventions to reduce second stroke risk are complex. For effective translation into practice, interventions must be specific to end-user needs and described in detail for replication. This study used an Integrated Knowledge Translation (IKT) approach and the Template for Intervention Description and Replication (TIDieR) checklist to co-design and describe a telehealth-delivered diet program for stroke survivors. Stroke survivors and carers (n = 6), specialist dietitians (n = 6) and an IKT research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(49 citation statements)
references
References 67 publications
(103 reference statements)
0
49
0
Order By: Relevance
“…We then conducted a word frequency analysis using the Word Frequency Analyser 33 on the titles, abstracts and keywords of three articles which were considered potentially includible, 24,38,39 and we considered for inclusion the terms identified by the Word Frequency Analyser by consensus. The search strategy was drafted for Medline (PubMed), consulted with the entire author team, and further refinements were made.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…We then conducted a word frequency analysis using the Word Frequency Analyser 33 on the titles, abstracts and keywords of three articles which were considered potentially includible, 24,38,39 and we considered for inclusion the terms identified by the Word Frequency Analyser by consensus. The search strategy was drafted for Medline (PubMed), consulted with the entire author team, and further refinements were made.…”
Section: Search Strategymentioning
confidence: 99%
“…16 Only three of the included studies [17][18][19] reached 'collegiate' levels of participation, defined as 'researchers and local people work(ing) together as colleagues with different skills to offer, in the process of mutual learning where local people have control over the process'. 16 Furthermore, key co-design studies were not included in the review, [20][21][22][23][24] and due to the rapid increase in co-design studies, even in the past 2 years, we have identified several recent studies that considerably add to the literature involving co-design for nutrition interventions.…”
Section: Introductionmentioning
confidence: 99%
“… 15 However, it is important to note that no studies to date 16 report engaging consumers with FA in the development of the intervention. Several studies in the areas of diabetes, 17 mental health, 18 asthma 19 and stroke 20 21 have reported on the benefits of adopting a codesign approach to help generate more relevant and actionable intervention research. Within the context of FA, which has been found to be positively associated with co-occurring mental health conditions such as depression, anxiety, eating disorders 7 22–24 and severe mental illness including schizophrenia and bipolar affective disorder, 25 developing treatment options in combination with health professionals and consumers with lived overeating experiences through a codesign process may be of benefit, and assist with improving translation for clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“… 33 Both of these frameworks aim to improve research quality 34 and allow researchers to choose appropriate methods 35 increasing reproducibility and validity of studies. 20 However, systematic reviews have indicated that few interventions are meeting these guidelines. 36–39 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation